Characterizing Extracurricular Effort on Concurrent and Distributed Programming Learning - Hidalgo-Cespedes, Jeisson (2019 IV Jornadas Costarricenses de Investigación en Computación e Informática (JoCICI), 2019)
The importance of concurrent and distributed programming is increasing on Computer Science curricula. This exploratory research identifies additional notions required by the official topics of "Parallel and Concurrent Programming" course, taught at the University of Costa Rica. This paper characterizes previous knowledge that students had about these notions and the extracurricular effort that they made to overcome the lack of notions. Findings show that students were able to overcome the lack of notions at expense of more extracurricular effort. Exploratory evidence indicates that students' election of professors in previous courses influenced their performance and extracurricular effort in the parallel programming course.